2007
DOI: 10.1007/s00127-007-0161-8
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Hopkins Symptom Checklist-25 (HSCL-25) and the Self-Reporting Questionnaire (SRQ-20) as screening instruments used in primary care in Afghanistan

Abstract: This study underlines the necessity of validating instruments along with cultural context and gender. Earlier studies in Afghanistan may have overestimated the prevalence of mental disorders among women and underestimated the prevalence in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 34 publications
7
148
1
4
Order By: Relevance
“…In Afghanistan, for example, when high prevalence rates for anxiety and depression (as-sessed using standard mental health questionnaires) were compared with a standard psychiatric interview, results indicated that the optimal cut-off points should be higher than usual for women, but lower than normal for men; this suggested that earlier studies may have over-and underestimated prevalence rates respectively (Ventevogel et al, 2007). Although it is beyond the scope of the present study to accurately determine this, mean K-10 scores for men were 18.5 and for women were 21.8, so even if these were adjusted in line with these findings, means for both men and women would still fall within the moderate risk range, significantly higher than the local populations.…”
Section: Discussionmentioning
confidence: 99%
“…In Afghanistan, for example, when high prevalence rates for anxiety and depression (as-sessed using standard mental health questionnaires) were compared with a standard psychiatric interview, results indicated that the optimal cut-off points should be higher than usual for women, but lower than normal for men; this suggested that earlier studies may have over-and underestimated prevalence rates respectively (Ventevogel et al, 2007). Although it is beyond the scope of the present study to accurately determine this, mean K-10 scores for men were 18.5 and for women were 21.8, so even if these were adjusted in line with these findings, means for both men and women would still fall within the moderate risk range, significantly higher than the local populations.…”
Section: Discussionmentioning
confidence: 99%
“…We adjusted for any inflation to pooled prevalence by specifying that prevalence derived from diagnostic tools was the gold standard. This is consistent with the methodology used by other authors specifying that data from symptoms scales need to be 'recalibrated' relative to data from diagnostic tools (145,147,148). Despite some differences in the DSM and ICD definitions of MDD, diagnostic criteria did not have a statistically significant effect on prevalence.…”
Section: Discussionsupporting
confidence: 84%
“…There has been continuous debate as to whether symptom scales are better suited to measuring mental disorder symptoms or psychological distress (143)(144)(145) . In this case, we found that symptom scales inflated the overall prevalence of MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Hamilton Depression Rating Scale (Hamilton, 1960); Harvard Trauma Questionnaire (Shoeb et 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 al., 2007); Hopkins Symptoms Checklist-25 (Ventevogel et al, 2007); and the Post Migrational Living Difficulties Questionnaire (Silove et al, 1997).…”
Section: Assessment Measuresmentioning
confidence: 99%
“…The HSCL-25 has 10-items on anxiety symptoms and 15-items on depressive symptoms, which are scored from 1 (not at all) to 4 (extremely) (Ventevogel et al, 2007). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Finally, the Post Migrational Living Difficulties Questionnaire was used in two studies was used in six studies was used in two studies with a cumulative sample size of 349 (100% of whom met study inclusion criteria), and assessed levels of stress due to post migration stressors.…”
Section: Self-reportmentioning
confidence: 99%